Considering the military-media nexus from the perspective of competing groups: the case of ISIS and al-Qaeda in the Arabian Peninsula. Issue 1 (2nd January 2020) - Winkler, Carol; El-Damanhoury, Kareem; Dicker, Aaron; Luu, Yennhi; Kaczkowski, Wojciech; El-Karhili, Nagham
ABSTRACT: To address if and how militant, non-state actors in the online environment react to on-the-ground military pressures facing their competitors, this study explores AQAP's visual media campaign during the 2016–2017 military operations to retake Mosul and Raqqa from ISIS control. Using chi-square analyses and content analysis, we analyzed 4027 images from Inspire, Jihad Recollections, and al-Masra to reveal how the onset of the ISIS battles corresponded to changes in AQAP's strategic use of visual content, presentational form, and language-based audience targeting. Significant changes in visual content related to the display of institutional power structures rather than identity markers. Shifts in presentational elements involved image positioning (foreground/background) and viewer distance (intimate/personal vs. social public). Language-based targeting strategies between English and Arabic publications, however, demonstrated the most substantial change from before to during the battles. The study concludes that a complete understanding of the military-media nexus of militant, non-state groups requires consideration of military pressure on competing groups.